Faktor Resiko Sunat pada Perempuan : Scoping Review - Novia Renata Kiaymodjo; Hafizha Alya Kusumaningtyas; Rasnun Ruslan; Irawati Ipa; Cindy Fahrani Cuyuw; Atik Sunarmi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Female Genital Mutilation and Injury (FGM) or female circumcision is an old practice that is still widely practiced in various parts of the world, including Indonesia. Female circumcision is a process of removing or cutting half or all of the clitoris (clitoridectomy), removing the clitoris and half or all of the labia minora (excision), or cutting some or all of the extero-genital (outer genitals) by sewing or narrowing the vaginal area (infibulation). Female circumcision currently has no medical indication and has not been proven to have health benefits. Female circumcision is still widely practiced for various reasons, both cultural traditions and religious recommendations. The purpose of this study was to determine the risk factors for female circumcision. Research methods: This type of research uses a scooping review to identify literature in depth and comprehensively obtained from various sources with various research methods and interest in the research topic. Results: The results of this study state that female circumcision has several risk factors including bleeding, bacterial infection, can cause trauma and shock and reduce sexual sensitivity and libido. Female circumcision is just a tradition or culture in society where the act has no benefits and health basis. It is expected that monitoring of female circumcision or the practice of circumcision and seeking the latest information on circumcision in girls will be carried out in order to maintain the health of the community.